Attitudes towards transjugular intrahepatic portosystemic shunt (TIPS) in Australia: a national survey of TIPS centres - Jacob George; Avik Majumdar; Golo Ahlenstiel; Stuart K Roberts; Scott Read; Eric Kalo (BMJ Open Gastroenterology)
Background Transjugular intrahepatic portosystemic shunt (TIPS) is a minimally invasive therapeutic option to treat the sequelae of portal hypertension. It is unclear whether current international recommendations are reflected in current clinical practice across Australia and the extent of variations in care. This study aimed to address this gap in knowledge and benchmark the current landscape of TIPS services in Australia against international guidelines.Methods We designed a 42-item questionnaire according to practice-based recommendations and standards of international guidelines to investigate current landscape of TIPS service across four key domains: (1) service provision, (2) patient selection and indications, (3) best procedure practice, and (4) postoperative care.Results Gastroenterologist/hepatologists from 23 major liver centres (67.6%) across Australia currently performing TIPS completed the questionnaire. Between 2017 and 2020, there were 456 elective TIPS insertions. Units offering TIPS service had a low median number of TIPS insertions (n=7 per annum). More than half of respondents (56.5%) did not have institutional clinical practice protocols. There was marked variation in practices across institutions in terms of TIPS indications and patient selection. Despite variations, the success rate of elective TIPS was high at 91.7% (79–100%), with 86.6% (29–100%) for rescue TIPS. There was significant variation in postoperative follow-up and care.Conclusion Current TIPS practice in Australia varies significantly across institutions. There is a need for a national consensus clinical practice guidelines to improve access and minimise unwarranted variation. A national registry for TIPS could measure, monitor, and report on quality of clinical care and patient outcomes.